Timing of School Entry and Personality Traits in Adulthood - Anton Barabasch; Kamila Cygan-Rehm; Andreas Leibing (Institute of Labor Economics (IZA), 2024)
This paper investigates the long-run consequences of a later school entry for personality traits. For identification, we exploit the statutory cutoff rules for school enrollment in Germany within a regression discontinuity design. We find that relatively older school starters have persistently lower levels of neuroticism in adulthood. This effect is entirely driven by women, which has important implications for gender gaps in the labor market, as women typically score significantly higher on neuroticism at all stages of life, which puts them at a disadvantage. Our results suggest that family decisions regarding compliance with enrollment cutoffs may have lasting implications for gender gaps in socio-emotional skills.
Keywords: I21; I28; J24; D19; 330; school starting age; personality; socio-emotional skills; education